STUDENTS' PERCEPTIONS OF THE DANA APPLICATION'S EFFECTIVENESS - Asri, Agi Permata (REVIEW OF MULTIDISCIPLINARY EDUCATION, CULTURE AND PEDAGOGY, 2022)
This paper aims to investigate students' perspectives on the recognition and utilization of the DANA application. This study's participants were students who utilized the DANA application. This type of investigation is a context-based study. The information collection strategy employs summary techniques and Google online structures. It is revealed that risk insights have no effect on the intention to use the DANA application. Positive emotions and a helpful attitude have been shown to influence the intention using the DANA application. Nevertheless, positive emotions have been demonstrated to influence the perception of value, but not the perception of risk. Visible reliability is exhibited so as not to affect the perception of risk.